Resonant magnetic reflectivity from U/Fe multilayers - Brown, S; Beesley, A; Herring, A; Mannix, D; Thomas, M; Thompson, P; Bouchenoire, L; Langridge, S; Lander, G; Stirling, W; Mirone, A; Ward, R; et al. (2003)
The resonant magnetic reflectivity from U/Fe multilayers was analyzed. These multilayers were produced through dc sputtering and analyzed using techniques such as polarized neutron reflectivity, conversion electron Mössbauer spectroscopy and magneto-optic measurements. The reversal of the polarity of the asymmetry ratio between the first and second superlattice peaks between the first and second superlattice peaks indicates a nonuniform moment distribution through the uranium layers.